Phénomène migratoire, formation et différenciation des associations de hemşehri à Istanbul : chronologies et géographies croisées - Jean-François Pérouse (European Journal of Turkish Studies)
This paper seeks to compare the process of immigration to Istanbul and the different steps in the creation of ‘hometown associations’. Taking as its source a comprehensive official database (from the Turkish Minister of Internal Affairs) listing both the address and the name of this type of association, this paper aims to shed light on the development and inner shaping of the hemşehri associations system or network in Istanbul. This is done from two angles: firstly, a territorial perspective, and secondly, a structural one. In doing so, it becomes apparent that as regards the first level of the hemşehri associations system (that is to say the associations on a village scale) though there may be a strong link between the development process of associations and the migration process, this connection becomes increasingly lax for the others levels of the hemşehri association system (that is to say the associations on a district or a provincial scale).